Assessing thermal comfort in the Mediterranean social housing stock through test cells: Comparison of double-skin, externally insulated and non-retrofitted facades - Carmen María Calama-González; Ángel Luis León-Rodríguez; Rafael Suárez (Case Studies in Thermal Engineering, 2022)
Climate change will derive in severe repercussions to the built indoor environment, evidencing the importance of retrofitting buildings. Thus, the improvement of energy efficiency of facades is of the utmost relevance, given its representativeness in the total thermal envelope. The objective of this research is to provide a simultaneous comparison between a ventilated double skin facade and an unretrofitted solution, assessing their impact on thermal comfort of housing units under Mediterranean winter and summer conditions. To do so, on-site monitoring through test cells have been used, analysing different orientations and protocols, under the same weather conditions and with no users’ influence. Comfort results obtained have been compared with an externally insulated facade. Conclusions show that the double skin facade clearly performs better in summer, minimising indoor maximum peak temperatures, especially with outdoor temperatures above 35 °C. Yet, it may lead to indoor overheating during night-time. In winter, the double skin facade reports around 21.3% less comfort hours than an externally insulated facade, performing similarly to an unretrofitted solution towards maximum peak temperatures with outdoor values of 5–20 °C. However, it shows a better thermal performance under minimum peak temperatures, with up to 3 °C difference from the unretrofitted solution.